Board diversity and firm value: A study on Malaysian listed firms in manufacturing and non-manufacturing sectors - Razali, Mohd Waliuddin Mohd; Yi, Pan Xin; Nordin, Nordiana Ahmad; Muhammad, Anuar; Lunyai, Janifer (Asian Development Policy Review, 2023)
The main purpose of this study is to examine the relationship between board diversity and firm value in firms in the manufacturing and non-manufacturing sectors listed on Bursa Malaysia. The methodology of this study utilized 200 samples of Malaysian listed companies from 2014 to 2016. The board diversity variables in this study were gender, age, educational level, outsider director, and nationality. Diversity data were collected from the annual report, while all financial data, such as firm age, firm value, and firm leverage, were collected from the Eikon database. The findings show that educational level has a negative relationship with firm value, while outsider director has a positive relationship with firm value in the manufacturing sector. In the non-manufacturing sector, gender and nationality have positive relationships with firm value. In conclusion, the manufacturing industry needs outsider directors’ expertise to improve production operations. A higher level of education may lead directors to focus on fewer business aspects rather than the overall business. The non-manufacturing sector requires knowledge and skills that enhance customer satisfaction and thus increase firm value. The practical implication is that regulators such as Bursa Malaysia can enforce boardroom diversity through rules and regulations, which will affect firm value.